Validation of a questionnaire developed to evaluate the eating behavior of mexican travelers - López-Larios, Madeline de Jesús; Housni, Fatima Ezzahra; Martínez Moreno, Alma Gabriela; LLanes Cañedo, Claudia; Guizar Mateos, Isai; Padilla Galindo , Maria del Rocio; Barragan Carmona, María del Carmen (Progress in Nutrition, 2024)
Background and aim: Tourist travels are an excellent setting to study eating behavior's dimensions. Multiple factors of the food system can affect these dimensions, such as companions, food availability, weather, food environment, and lodging options. The Travelers' Feeding Behavior Change Questionnaire (TFBCQ) validated for Mexican Travelers (MxT) is a multidisciplinary analysis instrument that integrates different study areas: tourism, nutrition, and psychology for behavior analysis. The aim was to validate a virtual instrument to assess eating behavior in Mexican travelers based on theoretical constructs. Methods: The scale's content validity reached significant values when evaluated by expert judges, with moderate intensity in Kendall's W congruence (Kendall's W = 0.462; p = 0.000). Participants were 312 Mexican adults; 63% were women, 36% were men, 3% identified as gender fluid, and another 3% did not give gender information. We performed a factorial analysis (FA) with 53 items grouped into 12 factors, which explained 73% of the accumulated variance. Results: Factors in this questionnaire were (1) Consumption behavior before travel, (2) Eating behavior during outbound transfer, (3) Eating behavior during the stay, (4) Eating behavior during the return transfer, (5) Eating behavior back home, (6) consumption schedule, (7) consumption duration, (8) Consumption companion, (9) consumption motivation, (10) Physical Activity, (11) BMI, (12) Future consumption behavior. Cronbach's alpha value was 0.759. Conclusions: the TFBCQ questionnaire is an excellent instrument to evaluate changes in eating behavior in a feeding episode due to modification of spaces and temporalities in Mexican travelers.